HUBUNGAN KECANDUAN BERMAIN GAME ONLINE DENGAN KUALITAS TIDUR REMAJA - Nesha Nurdilla; Arneliwati Arneliwati; Veny Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Online game is a cyberspace game site connected by the internet network. An addiction to online games can cause a tremendous amount of consequences to the gamer such as forgot sleep, eat, and rest. This research aimed to determine the relationship between online game addiction with sleep quality of adolescence. This research used descriptive correlational design with cross sectional approach. This research was conducted on 70 samples at Junior High School 13 Pekanbaru used proportional stratified random sampling technique. The measuring tool used modified questionnaire that has been tested for validity and reliability. The data analysis used univariate and bivariate analysis to found the relationship between two variables studied using Chi-Square statistical test. The result of the research showed there was relationship between the online game addiction with sleep quality in adolescence with p value (0,002)< (0,05). This research expected to community especially adolescence to blame and control themselves in playing online game in attempt to avoid the impact on sleep quality of adolescence. Keywords: Adolescence, online games, online games addiction, sleep quality